Evaluation of Land Redistribution Policy Implementation in Sigi District, Central Sulawesi Province - Joko Wiyono; Muhammad Khairil; Ani Susanti; Sitti Chaeriah Ahsan; Hasbullah Hasbullah (Budapest International Research and Critics University, 2023)
This study aims to provide an overview and various facts related to the implementation of the Land Redistribution policy in Sigi Regency, Central Sulawesi Province from the aspects of effectiveness, efficiency, adequacy, alignment, responsiveness, and accuracy. The type of research used by the researcher is a qualitative descriptive type, the informants in this study were determined using a purposive technique. Techniques in collecting data, the authors use several ways of observation, interviews, and documentation. In this study, data were analyzed using several steps according to the theory of Miles, Huberman and Saldana (2014), namely analyzing data in three steps: data condensation, presenting data, and drawing conclusions or verification. Based on the results of the research, it can be concluded that the implementation of the policy of implementing the Land Redistribution policy in Sigi Regency, Central Sulawesi Province has not run optimally, this is because the effectiveness aspect has not gone well, because in 2022 the implementation of the Land Redistribution program in Sigi Regency has not reached the target. From the adequacy aspect, it has not gone well, because this policy is considered not sufficient to answer the socio-economic problems of the community, from the leveling aspect it has not fully gone well, because the distribution of information related to the program to the people in Sigi Regency has not been evenly distributed, even in its implementation in the field it also shows that there are still many also people who have not really felt the benefits of this policy. From the aspect of responsiveness it has not gone well, this is shown by the lack of enthusiasm of some people in Sigi Regency for the existence of the Land Redistribution program. In addition, the aspect that is going well is the aspect of efficiency, where the BPN is able to make the best use of the limited budget and human resources to achieve optimal results, and accuracy is also going well where this policy is very appropriate in responding to the agrarian problems that are in the midst of the community, especially the people of Sigi Regency, and not only that, the implementation in the field has been right on target.